Can transcranial electrical stimulation improve learning difficulties in atypical brain development? A future possibility for cognitive training - Krause, B; Cohen Kadosh, R (2013)
Learning difficulties in atypical brain development represent serious obstacles to an individual's future achievements and can have broad societal consequences. Cognitive training can improve learning impairments only to a certain degree. Recent evidence from normal and clinical adult populations suggests that transcranial electrical stimulation (TES), a portable, painless, inexpensive, and relatively safe neuroenhancement tool, applied in conjunction with cognitive training can enhance cognitive intervention outcomes. This includes, for instance, numerical processing, language skills and response inhibition deficits commonly associated with profound learning difficulties and attention-deficit hyperactivity disorder (ADHD). The current review introduces the functional principles, current applications and promising results, and potential pitfalls of TES. Unfortunately, research in child populations is limited at present. We suggest that TES has considerable promise as a tool for increasing neuroplasticity in atypically developing children and may be an effective adjunct to cognitive training in clinical settings if it proves safe. The efficacy and both short- and long-term effects of TES on the developing brain need to be critically assessed before it can be recommended for clinical settings. © 2012 Elsevier Ltd. All rights reserved.